Electronegativity in Substituted-4(H)-quinazolinones Causes Anxiolysis without a Sedative-hypnotic Adverse Reaction in Female Wistar Rats - Mishra, Shweta; Das, Debashree; Sahu, Adarsh; Verma, Ekta; Patil, Shailendra; Agarwal, Ram K.; Gajbhiye, Asmita (Central Nervous System Agents in Medicinal Chemistry, 2020)
Objective: In the current study, the synthesis, characterization, and neuropharmacology of quinazolinone tethered with aromatic (3a-3i) and heteroaromatic substitution (3j, 3k, and 3l) as effective anxiolytic agents are reported. Background: Anxiety and depression are often comorbid with neurological as well as other medical maladies. Clinically known anxiolytics (Benzodiazepines) are accompanied by untoward sedation and other CNS depressive actions. The quinazolinone moiety is a privileged pharmacophore with a wide pharmacological spectrum. Herein, the synthesis, characterization, and neuropharmacological evaluation of some 2-substituted quinazolinone derivatives are reported. Methods: The synthesized compounds were characterized using 1H-NMR and TLC analysis. Behavioral analysis was performed using EPM (Elevated Plus Maze), OFT (Open Field Test), PIST (Pentobarbital Induced Sleep Test), FST (Forced Swim Test) and PCPA (p-chlorophenyl alanine) bioassay. To further justify the therapeutic claim, systemic and neurotoxicological analysis of the most potent members of the series was performed using OECD mandated protocols. The studies showed that the compounds had a wide therapeutic window with >1000 mg/kg and >500 mg/kg LD50 and NOAEL, respectively. Results: The compounds with an electronegative group in the quinazolinone nucleus (3f, 3e, 3d, and 3c) induced anxiolysis devoid of sedative adverse reaction. Besides, anti-depressant efficacy of 3f, 3e, 3d, and 3c observed in rodents was a result of a decrease in anxiety level. It was found that the neurotoxicology of the potent members (3f, 3e, 3d, and 3c) advocated their wide therapeutic window with >1000 mg/kg LD50 and >5000 mg/kg NOAEL. Conclusion: Our findings of behavioral bioassays revealed that inducing an electronegative group into the quinazolinone nucleus yielded the most potent members of the series (3f, 3e, 3d, and 3c). The said compounds were found to produce anxiolysis and anti-depressive action without sedative-hypnotic side effects in rodent models. In summary, it can be stated that extending the studies in a clinical setting would furbish the contours of current anxiolytic therapy, especially in anxiety comorbid with medical maladies.
Keywords: anti-depressant like action